The intangible cultural heritage as a creative tourism product. The masks of Trás-os-Montes - Rodrigues, Cristina (2022)
Many regions of the world and in particular Portugal, are associated with products, symbols, crafts, and traditions. These associations help to build the identity image of places and the perception we have of them as tourism destinations. This article aims to present theoretical reflections on the potential of intangible cultural heritage for the construction of creative tourism products, in an inland region of Portugal, with a particularly rich and dynamic tradition in socio-cultural terms. The study applies to Terras de Trás-os-Montes, where it is believed that several tourism products, of creative basis, may emerge from the Tradition of Masked: an ancestral intangible cultural heritage, common to several municipalities of the region. Using the qualitative methodology, the interview method was applied, to understand the perspective of individuals with relevant knowledge about the issue. The results presented, link Tradition to the enhancement of cultural identity, the development of tourism activity, the focus on creative tourism, and the dynamics of cross-border cooperation. These themes highlighted the importance and the positive contribution of this cultural heritage, internally, to the resident community and externally, to the tourism market.